Hidden Secrets of ‘Punica Granatum’ Use and Its Effects on Oral Health: A Short Review - Rajan, Sukanya; Ravi, J; Suresh, Aparna; Guru, Sanjeela (Journal of Orofacial Research, 2013)
The interest in evaluating therapeutic effects of plants has increased dramatically with more and more people inclining toward alternative medicine for their health care needs as they are effective, nontoxic, economical and usually have no sideeffects. Pomegranate is one such fruit/ plant which is beneficial with added effect on oral health. This plant source of polyphenols has antioxidant properties, meaning they help protect cells from damage and may lower the inflammation in the body. Apart from this various other components of the pomegranate plant such as flowers are rich source flavonoids. Peel extracts have been demonstrated to have antibacterial and antifungal activity due to the presence of hydrolysable tannins and polyphenols. The stem part is known to have astringent and antihelminthic properties and the leaves have been used for conjunctivitis. Thus, the purpose of this review is to summarize the therapeutic benefits of various extracts derived from the pomegranate plant and its benefits on oral health.